Serine synthesis and transport mediate the synergistic and detoxifying effects of lienal peptides on cisplatin - Ding, Ke; Yu, Tengjie; Zhang, Xiaowei; Hu, Kangrui; Mao, Shuying; Zhang, Tingting; Liu, Ye; Wang, Zhongbo; Fan, Xin; Liu, Wei; Zhang, Dianzhui; He, Laipeng; et al. (Frontiers in Pharmacology, 2026)
Lienal peptides (LPs), one kind of animal-derived traditional Chinese medicine, are used clinically as an adjunctive therapeutic drug in oncology. Cisplatin (DDP) is a broad-spectrum chemotherapy drug widely used for non-small cell lung cancer (NSCLC) but is limited by a series of toxic side effects. To date, the feasibility of using LPs and DDP in combination remains unclear. The present study aimed to explore the feasibility of LPs combined with DDP as an adjuvant therapy for NSCLC by examining the effects of LPs on the efficacy and toxicity of DDP. Our findings demonstrated that LPs exhibited significant antitumor activity in Lewis lung carcinoma (LLC)-bearing mice when administered either alone or combined with DDP. Moreover, LPs treatment notably improved survival rate, alleviated renal and hepatic impairment, and reversed DDP-induced metabolic disorder. Additionally, our data indicated that tumor growth led to dysregulated serine metabolism. LPs could significantly normalize serine levels by modulaitng the synthesis of serine in gut microbiota and its SFXN1-mediated transport in tumor cells. Thus, this study for the first time reveals the auxiliary anti-tumor effect of LPs from the perspective of amino acid metabolism, supporting LPs as a promising adjuvant to DDP in NSCLC.